The expansion of newborn neurons in hippocampus improves social recognition deficit in a mouse model of autism - Meng, Hu; Li, Qiongwei; Wang, Jinxin; Yue, Weihua; Zhang, Dai; Sun, Xiaoxuan; Wang, Lifang; Li, Jun (Frontiers in Psychiatry, 2023)
Introduction Autism spectrum disorders (ASDs) are a group of neurodevelopmental disorders characterized by core symptoms of impaired social interaction and communication. The pathological mechanism and treatment are not clear and need further study. Our previous study found that the deletion of high-risk gene Autism Susceptibility 2 (AUTS2) in mice led to dentate gyrus (DG) hypoplasia that highly associated with impaired social novelty recognition. Here we aim to improve the social deficit through increasing the neurogenesis in the subgranular zone (SGZ) and expanding the newborn granule neurons in DG. Methods Three approaches including repeated oxytocin administration, feeding in enriched environment and overexpression of cyclin-dependent kinase 4 (Cdk4)-CyclinD1 complex in DG neural stem cells (NSCs) at the post-weaning stage were conducted. Results We found that the number of EdU labeled proliferative NSCs or retrovirus labeled newborn neurons was significantly increased after manipulations. The social recognition deficit was also significantly improved. Discussion Our findings suggested a possible strategy to restore the social deficit through expansion of newborn neurons in hippocampus, which might provide a new insight into the treatment of autism.